TaSnRK3.23B, a CBL-interacting protein kinase of wheat, confers drought stress tolerance by promoting ROS scavenging in Arabidopsis - Feiyan Dong; Yide Liu; Huadong Zhang; Yaqian Li; Jinghan Song; Sheng Chen; Shuailei Wang; Zhanwang Zhu; Yan Li; Yike Liu (BMC Plant Biology)
Abstract Background Sucrose non-fermenting-1-related protein kinases (SnRKs) have been implicated in plant growth and stress responses. Although SnRK3.23 is known to be involved in drought stress, the underlying mechanism of resistance differs between Arabidopsis and rice, and little is known about its function in wheat. Results In the current work, TaSnRK3.23B was detected on the cell membrane and in the nucleus. TaSnRK3.23B overexpression in Arabidopsis promoted reactive oxygen species (ROS) scavenging via the accumulation of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) and then conferred significant tolerance to drought. The prediction analysis, yeast two-hybrid, and bimolecular fluorescence complementation (BiFC) assays revealed that TaSnRK3.23B interacted with TaCBL2B and TaCBL6B, which are calcineurin B-like (CBL) proteins. The predicted model demonstrated that TaSnRK3 subfamily proteins participate in Ca2+ signaling mediated by TaCBL2B/TaCBL6B and subsequently provide drought stress tolerance by promoting ROS scavenging in wheat. Conclusions Altogether, the obtained findings contribute to a better understanding of the functions of SnRK3.23 in wheat and offer genetic suggestions for improving drought resistance of wheat.